Promoting Psychological Resilience in the U.S. Military - Meredith, Lisa S.; Sherbourne, Cathy D.; Gaillot, Sarah J.; Hansell, Lydia; Ritschard, Hans V. (RAND Corporation, 2023)
As U.S. service members deploy for extended periods on a repeated basis, their ability to cope with the stress of deployment may be challenged. Many programs are available to encourage and support psychological resilience among service members and families. However, little is known about these programs' effectiveness. This report reviews resilience literature and programs to identify evidence-informed factors for promoting resilience.